Kemampuan Literasi Matematis Mahasiswa Melalui Model Problem-Based Learning Menggunakan Klinometer - Adi Asmara; Zachriwan Zachriwan (Institut Agama Islam Negeri Curup, 2021)
This study aims to determine students' mathematical literacy skills through problem-based learning using a clinometer. This research method is quasi-experimental with the research design used is one group pretest-posttest analysis on the initial test obtained results which indicate that the two classes are normally distributed and homogeneous, this means that the two classes are in the same condition or circumstances, namely the ability mathematical literacy so that it can be treated. The final test is also normally distributed and homogeneous, but there is an average difference from the aspect of mathematical literacy skills taught using problem-based learning and conventional learning models. Then the analysis was carried out through the one-way ANOVA hypothesis test, it was obtained that there were significant differences in the two classes. Then proceed with the Scheffe test to see the differences between the two classes, it turns out that there are differences in students' mathematical literacy abilities in the experimental class and the control class. This means that the mathematical literacy ability of the problem-based learning model using a clinometer is higher than the mathematical literacy ability of students using conventional learning models.